Parallel processing of T cells and natural killer cells to enhance in vivo CAR T cell activity against blood and solid cancers - Lachlan J Dobson; Patrick W Marron; Ariana HT Drabble; Thiloma D Liyanage; Kristine C Pe; Clare Y Slaney; Barry D Hock; Alexander D McLellan (Clinical & Translational Immunology, 2026)
Abstract Objectives Despite their anti‐cancer properties, natural killer (NK) cells are discarded during CAR T cell manufacturing. NK cells display promising responses as a cell therapy, exhibiting remarkable safety at high doses. Moreover, NK cells have complementary cytokine profiles and distinct antigen‐recognition pathways to supplement CAR T cell therapies. We demonstrate parallel expansion of NK cells from the normally discarded PBMC of CAR T cell production for downstream combination therapies against solid and blood‐borne malignancies. Methods CAR T cells were manufactured from buffy coats with initial isolation of T cells from PBMC. NK cells were rapidly expanded in parallel by stimulating the remaining PBMC with membrane‐bound (mb)IL‐21 + mbIL‐15 feeder cells. Expanded NK cells were assessed through spectral flow cytometry and applied as a pretreatment prior to CAR Tcell infusion against xenograft tumor models in NOD‐ scid IL2Rgamma null (NSG) mice. Results Applying feeder cells to residual PBMC stimulated 5000‐fold expansions of pure NK cells. Expanded NK cells expressed various activation receptors and displayed strong in vitro cytotoxicity, which was further improved in CAR T‐conditioned medium. A pretreatment of NK cells enhanced existing CAR T cell therapies, improving in vivo tumor clearance and survival against breast cancer, acute lymphoblastic leukaemia and non‐Hodgkin's lymphoma. While NK cells eliminated CD19 −/− variants in vitro , they were unable to suppress antigen‐escape relapse in vivo . Conclusion This study encourages the optimal use of leukapheresis product. By recycling discarded PBMC into NK cells, CAR T cell therapies can be effectively enhanced, improving tumor clearance and survival.